If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3s + 4) = 222 Reorder the terms: 6(4 + 3s) = 222 (4 * 6 + 3s * 6) = 222 (24 + 18s) = 222 Solving 24 + 18s = 222 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 18s = 222 + -24 Combine like terms: 24 + -24 = 0 0 + 18s = 222 + -24 18s = 222 + -24 Combine like terms: 222 + -24 = 198 18s = 198 Divide each side by '18'. s = 11 Simplifying s = 11
| 4x+5=7x-9 | | (a-7)*2= | | X^4-6x+1=0 | | 2w+8x+11y+5w+3x-3y= | | (u+2)*8= | | (q-6)*2= | | (e+3)*2= | | 4x^2+28x+4y^2+8y-91=0 | | -7(2t+7)=-21 | | 10(s-3)=-111 | | 5(2l+8)=140 | | 4(a-5)=48 | | 77x^2+24x-5=0 | | (2p+3)(3.8)=(6-p)(2.4) | | x^4-x^3-38x^2-12x+100=0 | | 1.6=4y+15.2 | | -3(2x+3)=-2x+1 | | -5x-13=y | | 22.3-z=17.9 | | (x^2)-8=0 | | (y-5)-(y-2)=6y | | -2-9x=(5x-2) | | 28+4x=-12 | | 7squared=5x | | Y/2=48 | | 13k^2+36k-24=0 | | x(x^3-4)=0 | | f^2+3f+9= | | X^2-sqrt(4x)=0 | | 1-5r=-2r^2 | | 2x^2+15x+10=0 | | -5-5x-8x=-18 |